Formation of high-quality knowledge navychek s self students techno- pedagogic universities through educational complexes for CNC in teaching the course (Pedagogy of Higher and Secondary Education, 2012)
Zherdev V., Mosolov V. Formation of high-quality knowledge navychek s self students techno-pedagogic universities through educational complexes for CNC in teaching the courseThe pace of the current state of scientific – technical progress includes the introduction of modern high-tech education teacher training teachers. One of the new technologies for teaching students profile is the use of educational facilities of numerically controlled (CNC), which will optimize the process of education and enhance professional competence of students.
Keywords: computeryuteryzatsiya; automation; new technolos; increasing knowledge and skills of the students; the system numerical control (SCHPK); self-control; methods of independent work